A Highly Sensitive Nonenzymatic Sensor Based on Fe2O3 Nanoparticle Coated ZnO Nanorods for Electrochemical Detection of Nitrite. Issue 22 (11th September 2017) - Ahmad, Rafiq; Ahn, Min‐Sang; Hahn, Yoon‐Bong
Abstract: Monitoring of nitrite is needed for the management of nitrite contamination and to ensure the welfare of environment and human health. Hence, it is important to develop high‐performance sensors that precisely measure nitrite concentration. Herein, the fabrication of a highly sensitive nonenzymatic nitrite sensor based on Fe2 O3 nanoparticle coated ZnO nanorods (Fe2 O3 NP coated ZnO NRs) is demonstrated. The ZnO NRs are grown on a seeded silver electrode by a hydrothermal method and then coated under optimized conditions with Fe2 O3 NPs using a dip‐coating method. Detailed material characterizations and sensor fabrication process are reported. The electrochemical properties of a fabricated nonenzymatic nitrite sensor are tested with different concentrations of nitrite, which indicates that the coating of ZnO NRs with Fe2 O3 NPs significantly enhances the electrocatalytic activity. The sensor responds linearly with increasing concentration of nitrite from 1 to 1250 × 10 −6 m with a high sensitivity (131.2 µA µM −1 cm −2 ) and low detection limit (0.015 × 10 −6 m ). Moreover, excellent selectivity, stability, and reproducibility allow using these sensors for the determination of nitrite concentration in water with satisfactory results. Abstract : A highly sensitive nonenzymatic nitrite sensor is successfully fabricated using Fe2 O3 nanoparticle coated ZnO nanorods and employed for electrochemical detection of nitrite. The ZnO nanorod surface modification with Fe2 O3 significantly improves the electrocatalytic activity for nitrite oxidation. As a result, enhanced sensing performance and potential application of fabricated sensor in real complex water samples are attained for nitrite detection.